Spheriacal radiotelescope surface adjustment using arbitrary located laser rangefinder - A. R. Khachatryan (ՀՀ ԳԱԱ հրատ.)
Surface deviations from the given form in a reflector antenna reduce the aperture efficiency. In this paper we have developed a mathematical foundation and modeled a method of measuring the reflector roughness of a radio telescope.Անտենայի հայելու մակերևութային անհարթությունները զգալի բացասական ազդեցություն են թողնում անտենայի օ.գ.գ.-ի վրա։ Ստեղծվել են մաթեմատիկական հաշվարկային բանաձևեր և ծրագրային մոդելավորման մեթոդներ՝ ռադիոաստղադիտակի հայելու անհարթությունները գնահատելու համար։ Поверхностные отклонения отражателя антенны от данной формы уменьшают коэффициент полезного действия антенн. Разработаны математические формулы и методы моделирования для измерения неровностей поверхностей отражателя радиоте- лескопа.
Keywords: Electrical engineering; Electronics; Nuclear engineering; Technology